Politik Kejutan: Analisis Wacana Kritis Penggunaan Kata 'KAGET' oleh Presiden Jokowi dalam Komunikasi Politik 2014-2024 - Febriandy, Radians Krisna (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research focuses on President Joko Widodo's use of the word "KAGET" in political discourse during the period 2014 to 2024. The use of this word often appears in response to various unexpected events and has become an important part of building Jokowi's leadership image. The purpose of this study is to analyze how the word "KAGET" is used as a political communication strategy. The method used is Critical Discourse Analysis (CDA) based on Norman Fairclough's model, which includes text analysis, discursive practices, and social practices. Data were taken from various media that reported Jokowi's statements in different contexts. The results show that the word "KAGET" plays a role in building Jokowi's image as a leader who is adaptive, honest, and close to the people. However, in some cases, this word is also criticized as a sign of unpreparedness. In conclusion, Jokowi's use of the word "KAGET" strengthens emotional connections with the people, manages public expectations, and provides political flexibility in responding to crises.